Relationship between age and handgrip strength: Proposal of reference values from infancy to senescence - Gómez-Campos, Rossana; Vidal Espinoza, Rubén; de Arruda, Miguel; Ronque, Enio Ricardo Vaz; Urra-Albornoz, Camilo; Minango, Juan Carlos; Alvear-Vasquez, Fernando; la Torre Choque, Christian de; Castelli Correia de Campos, Luis Felipe; Sulla Torres, Jose; Cossio-Bolaños, Marco (Frontiers in Public Health, 2023)
Introduction Measurement of hand grip strength (HGS) has been proposed as a key component of frailty and has also been suggested as a central biomarker of healthy aging and a powerful predictor of future morbidity and mortality. Objectives (a) To determine whether a nonlinear relationship model could improve the prediction of handgrip strength (HGS) compared to the linear model and (b) to propose percentiles to evaluate HGS according to age and sex for a regional population of Chile from infancy to senescence. Methods A cross-sectional descriptive study was developed in a representative sample of the Maule region (Chile). The volunteers amounted to 5,376 participants (2,840 men and 2,536 women), with an age range from 6 to 80 years old. Weight, height, HGS (right and left hand) according to age and sex were evaluated. Percentiles were calculated using the LMS method [(L (Lambda; asymmetry), M (Mu; median), and S (Sigma; coefficient of variation)]. Results and discussion There were no differences in HGS from 6 to 11 years of age in both sexes; however, from 12 years of age onwards, males presented higher HGS values in both hands (p < 0.05). The linear regression between age with HGS showed values of R2 = 0.07 in males and R2 = 0.02 in females. While in the non-linear model (cubic), the values were: R2 = 0.50 to 0.51 in men and R2 = 0.26 in women. The percentiles constructed by age and sex were: P5, P15, P50, P85, and P95 by age range and sex. This study demonstrated that there is a nonlinear relationship between chronological age with HGS from infancy to senescence. Furthermore, the proposed percentiles can serve as a guide to assess and monitor upper extremity muscle strength levels at all stages of life.